1999
DOI: 10.1097/00004872-199917010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of endothelin receptors in hypertensive resistance vessels

Abstract: The higher vasoconstriction induced by endothelin-1 in SHR may be related to a greater number of available ETA receptors, due to the presence of an ETA receptor subtype. This mechanism may be linked to the production of prostanoids that add to the direct endothelin-1-evoked vasoconstriction. These results, together with the lack of relaxation in response to sarafotoxin S6c in SHR, suggest that an imbalance in the endothelin-1 ability to induce both contraction and relaxation is present in SHR with sustained hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…We used 12-wk-old male SHR as a genetic model of hypertension and compared them with male WKY control rats. Consistent with previous studies (37,40), our SHR had significantly higher SBP and weight than agematched WKY rats (Table 1). Although SHR were hypertensive, they were not diabetic, because fasting plasma glucose concentrations were normal and comparable to those of WKY rats.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We used 12-wk-old male SHR as a genetic model of hypertension and compared them with male WKY control rats. Consistent with previous studies (37,40), our SHR had significantly higher SBP and weight than agematched WKY rats (Table 1). Although SHR were hypertensive, they were not diabetic, because fasting plasma glucose concentrations were normal and comparable to those of WKY rats.…”
Section: Resultssupporting
confidence: 92%
“…After equilibration (30 -40 min), changes in perfusion pressure were measured with a pressure transducer system (SP 844 Capto, Horten, Norway) and recorded continuously using data acquisition and analysis equipment (PowerLab system; ADInstruments, Castle Hill, Australia). Endothelium removal was performed by flushing vessels intermittently with air for several minutes as previously described (37) and was verified by complete lack of vasodilation induced by infusion of 1 M acetylcholine (ACh; Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study we have observed a depressed responsiveness to endothelin-1 in hypertensive patients, compared with normotensive subjects, thus con rming the majority of previous reports [18,[37][38][39][40][41][42], albeit in two studies enhanced endothelin-dependent responses were observed in SHR [43,44], and in one also in subcutaneous small resistance arteries of hypertensive patients [45]. Therefore, some controversy exists about this issue.…”
Section: Discussionsupporting
confidence: 89%
“…In patients with essential hypertension and in spontaneously hypertensive rats, ET-1 caused constriction of resistance blood vessels that was highly dependent on COXderived constrictor mediators. [43][44][45] This COX dependency was not observed in normotensive subjects and was not observed during ␣-adrenergic constriction. 43,44 ET-1 or phenylephrine caused similar vasoconstrictor responses in hypertensive and normotensive patients.…”
Section: Discussionmentioning
confidence: 74%
“…[43][44][45] This COX dependency was not observed in normotensive subjects and was not observed during ␣-adrenergic constriction. 43,44 ET-1 or phenylephrine caused similar vasoconstrictor responses in hypertensive and normotensive patients. 44 However, after COX inhibition, constriction to ET-1 (but not phenylephrine) was dramatically reduced in hypertensive compared with normotensive individuals.…”
Section: Discussionmentioning
confidence: 74%